FAKTOR-FAKTOR YANG MEMPENGARUHI TAX AVOIDANCE DENGAN LEVERAGE SEBAGAI VARIABEL MEDIASI - Deny Tristianto; Rachmawati Meita Oktaviani (Faculty of Economic and Business Universitas STIKUBANK, 2016)
This research aimed to examine and analyze the effect of executive characteristic, size, sales growth, and leverage towards corporate tax avoidance. On this research, leverage used as mediating variabel to mediate the relationship between executive charactheristic, size, and sales growth to corporate tax avoidance. The population in this research is manufacturing companies listed on the Indonesian Stock Exchange period 2012 to 2014. The sampling technique was done by purposive sampling with sample data which gathering of this research was 129. Data was processed by SPSS software using multiple regression analysis and path analysis. The result of this research showed that executive characteristic, size, sales growth, and leverage had a significant effect to tax avoidance. Based on path analysis, leverage as mediating variabel can’t mediate the relationship between executive characteristic to tax avoidance, but it can mediated the relationship between size and sales growth to tax avoidance in the company. Keywords: executive characteristic, size, sales growth, leverage, tax avoidance